Right ventricular longitudinal strain with CMR can more accurately estimate right ventricular functional reserve in rats with pulmonary arterial hypertension. (25th November 2020) - Sato, H; Someya, Y; Takahashi, Y; Kumasaka, K; Sato, W; Nishiyama, M; Matsumoto, A; Morita, N; Shindoh, C; Ota, H; Ueda, T; Kawashima, R; et al.
Abstract: Background: Right ventricular (RV) function is an important prognostic factor in patients with pulmonary arterial hypertension (PAH). Recently, CMR has become an attractive modality for follow up and providing prognosis in the patients, and strain has been used as a newer parameter to assess contractile properties of ventricle. It has not yet been established, however, whether RV strain with CMR can estimate RV functional reserve in the patients with PAH. Purpose: We focused on CMR imaging of RV, investigating whether RV longitudinal strain can estimate RV functional reserve using a rat model with PAH. Method: Rats were given a subcutaneous injection of 60 mg/kg monocrotaline (MCT-rats) or solvent (Ctr-rats). Four weeks after the injection, 25% of MCT-rats died due to RV failure. In the survivors of MCT- (n=19) and Ctr-rats (n=5), retrospective ECG-gated cine MR (16 phases/beat) was imaged with a 7T scanner. Subsequently, we measured RV pressure (RVP) via right internal jugular vein and dissected trabeculae (length = 1.45±0.07 mm, width = 334±27 μm, thickness = 114±6 μm) from RVs. We calculated weight ratio of RV free wall to left ventricle (LV) by RV/(LV+septum). Trabeculae were electrically stimulated with 2-s stimulus intervals, and force was measured using a silicon strain gauge (0.7 mM extracellular Ca2+, 24°C). To determine contractile properties of RV muscle, dF/dt was calculated. Using CMR imaging, we measured RV ejection fraction (RVEF) and RV longitudinal strain (RVLS). To modulate RVP, we intravenously injected 5 nmol endothelin-1 (ET-1) and again measured RVEF and RVLS. Results: MCT-rats showed higher systolic RVP (62.5±16.6 vs. 25.9±1.86 mmHg, p<0.01) and higher weight ratio of RV (0.60±0.03 vs. 0.28±0.02, p<0.05). In CMR imaging, MCT-rats showed lower RVEF (36.1±11.2 vs. 64.8±8.4%, p<0.001) and lower RVLS (−18±9 vs. −30±1%, p<0.05). In trabeculae from RVs, MCT-rats showed lower developed force and lower dF/dt (p<0.01). Correlation between RVLS and dF/dt was higher (n=20, r=0.53, p<0.05) than that between RVEF and dF/dt (r=0.24). In addition, RVLS and dF/dt had already been decreased in 5 MCT-rats with relatively preserved RVEF (>50%), suggesting that RVLS decreases earlier than RVEF in MCT-rats. Ten minutes after the injection of ET-1, RVP was increased from 49.4±7.9 to 57.9±6.4 mmHg in MCT-rats (n=6). In MCT-rats with preserved RVEF and decreased RVLS, the increase in RVP chiefly decreased RVEF while it did not change RVLS and RVEF in Ctr-rats, meaning that RV functional reserve had been decreased in MCT-rats. In trabeculae, developed force and dF/dt were increased after the addition of 0.1 μM ET-1 in MCT- (n=11, p<0.01) and Ctr-rats (n=4, p<0.01). Conclusion: These results suggest that in rats with PAH, RVLS obtained from CMR can estimate RV functional reserve earlier and more accurately than RVEF. Therefore, RV strain with CMR may become an important parameter to assess RV functional reserve in patients with PAH. Funding Acknowledgement: Type of funding source: Public grant(s) – National budget only. Main funding source(s): Grant-in-Aid for Young Scientists